Religion without Transcendence?
X, 292 p.
Keywords: What can transcendence mean for us? We live in a world in which there are many conceptions of transcendence. Some philosophers say that they all point, in their way, to a transcendent realm, without which death and life's sorrows have the last word, while their opponents argue that since this realm is an illusion, we must use our own resources to meet life's trials. Others argue that moral and religious concepts of transcendence are obscured by philosophical notions of transcendence, and must be rescued from them. These conflicting views on a central issue in our culture are brought into sharp relief in the present collection.